2021
DOI: 10.1177/00031348211024232
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care for Extracorporeal Life Support: Insights From the National Inpatient Sample

Abstract: Background Providing temporary cardiopulmonary support, extracorporeal membrane oxygenation (ECMO) carries a high risk of mortality. Palliative care (PC) may facilitate a patient-centered approach to end-of-life care in order to aid symptom management and provide psychosocial support to families. The present study aimed to identify factors associated with PC consultation and its impact on resource utilization in ECMO. Study Design All adults placed on ECMO at a PC capable center were identified in the 2006-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 6 PCC is already utilized in about 19% of ECMO cases in the US for patients on ECMO for respiratory failure, cardiogenic shock, thoracic transplantation, amongst other indications. 7 Various studies highlight the prolonged hospitalization course of both survivors and decedents requiring ECMO for COVID, often over a month. 8 , 9 PCC is known to play a role in the care of patients with chronic critical illness, and early integration may be helpful in family-centered ICU care when patients are on ECMO.…”
Section: Introductionmentioning
confidence: 99%
“… 6 PCC is already utilized in about 19% of ECMO cases in the US for patients on ECMO for respiratory failure, cardiogenic shock, thoracic transplantation, amongst other indications. 7 Various studies highlight the prolonged hospitalization course of both survivors and decedents requiring ECMO for COVID, often over a month. 8 , 9 PCC is known to play a role in the care of patients with chronic critical illness, and early integration may be helpful in family-centered ICU care when patients are on ECMO.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is supported by the results of a study by Emple et al ( 18 ). In this prospective study, moral distress was higher in nurses compared with physicians when caring for patients with mechanical circulatory support and coping strategies differed among the professions ( 19 , 20 ). Although nurses chose “increasing use of palliative care” as the most useful strategy to reduce moral distress, physicians most commonly selected “regular debriefing sessions” ( 18 ).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, some saw ECLS as just another intensive care measure, whereas others urgently demanded standardized sPC involvement of all ECLS patients due to the high mortality of this procedure. Even though the use of sPC in patients with extracorporeal systems increased in the past years, studies on sPC in CPR-ECLS are scarce ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…One such study found that PC consultation is not associated with higher cost or longer hospital length of stay in people who died during a hospitalization during which they received ECMO support. 32 Two additional studies analyzed PC utilization in patients on ECMO for whom WLST was requested. 15,19 Although these studies are useful in the context of patients who die while on ECMO, they focus on a subset of patients requiring ECMO support and fail to illustrate PC's utility in patients who are expected to survive.…”
Section: Discussionmentioning
confidence: 99%